(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Statistical process control (SPC) can help manufacturers improve the quality of their products. This paper describes a relatively simple and effective method and algorithm to adjust the accuracy of parts produced on CNC machine tools using the methods of statistical process control. Examined the possibilities of the proposed method by computer simulation of the process. By using the proposed algorithm scattering of size is placed in the middle of the tolerance zone. Various variants carrying out the method are proposed adequate on the machining time during processing details in the sample. This can optimize the total time for processing of the batch.